NATO ENLARGEMENT AND U.S. FOREIGN POLICY AFTER THE COLD WAR - Pradana, Muhammad Erza; Ghiffary Abdurrahman, Muhammad Kamil (Mandala: Jurnal Ilmu Hubungan Internasional, 2025)
In the aftermath of the Cold War, the United States not only sought to preserve the NATO alliance but also supported its eastward enlargement. Beginning in 1999, NATO welcomed new member states; most were from the former Soviet bloc. America’s support for NATO enlargement deserves scrutiny. Why did the United States support NATO enlargement even when the Cold War had ended? To answer such a question is to uncover the rationale behind America’s decision. This is what this research aims to do. Utilizing the publicly available archival materials from the administrations of George H.W. Bush and Bill Clinton and through a review of the scholarly literature, we argue that the U.S. decision to support NATO enlargement is largely consistent with the basic premise of offensive realism: that states are acutely aware of uncertainty and that they seek to maximize their power for security reasons. Notwithstanding the presence of liberal ideals, America’s support for NATO enlargement, in other words, did have sound strategic rationale.